PERTIMBANGAN HAKIM DALAM MEMERIKSA DAN MEMUTUS PERSELISIHAN PHK YANG DALUWARSA (STUDI PUTUSAN NOMOR 274/PDT.SUS-PHI/2019/PN BDG): Judges' Considerations in Examining and Deciding Disputes over Expired Layoffs (Study of Decision Number 274/Pdt.Sus-PHI/2019/PN Bdg) - Raindiyani, Rera Oktarisa; Pamungkas, Yogo (Faculty of Law, Universitas Trisakti, 2024)
Layoffs are the termination of employment relations due to certain circumstances that result in the end of rights and obligations between workers and the company. In decision number 274/Pdt.Sus-PHI/2019/PN Bdg, the judge accepted the defendant's exception stating that the plaintiff's actions exceeded the time limit. From the decision, the problem arises is whether the judge's consideration in the PHI decision stating that Lasman Tampubolon's lawsuit has exceeded the period of time is in accordance with applicable laws and regulations and whether the rights given by the Tri Bhakti Langlangbuana Education Foundation to Lasman Tampubolon are in accordance with Law No. 13 of 2003 concerning Manpower. To answer the problem, normative research is carried out which is analytical descriptive research and the type of data used is secondary data. It can be concluded that the judge's consideration that Lasman Tampubolon's lawsuit has exceeded the period in accordance with laws and regulations and the rights granted by the Tri Bhakti Langlangbuana Education Foundation are not in accordance with Law No. 13 of 2003 concerning Manpower.